One-Side Weight Sports and the Impact of Their Load on the Feet and the Occurrence of Posture Disorders in Professional Football and Handball Players - Matúš Kozel; Gabriela Škrečková; Marina Potašová; Peter Kutiš; Lenka Ondrušková (Applied Sciences)
The aim of this study was to evaluate center of pressure (CoP) changes in unilateral sports and examine how these changes affect the athlete’s feet, ankles, knees or posture. The study sample consisted of 40 professional male players (age: 19.4 ± 2.08 years; height: 165.78 ± 4.92 cm; weight: 59.04 ± 4.02 kg; BMI: 21.57 ± 2.22; foot size: 40.9 ± 1.6), divided by type of sport into group H—handball (n: 20) and group F—football (n: 20). To evaluate the monitored parameters, we used the instrumental diagnostic techniques: 3D laser footscan, baropodometric platform FreeStep and 2D Videography. We found no significant differences between the groups in the loading of the right and left foot (F: 8.3 ± 4.22; H: 7.7 ± 6.1) (p = 0.410). We found a significant difference in the load on the front and back of the left (p = 0.0079) and right foot (p = 0.0210) depending on the type of sport performed. Maximum and mean values of CoP (g/cm2) showed statistically significant differences depending on the sport performed (p < 0.0001). The shift in CoP (mm) from the norm depending on the sport performed was confirmed in the latero-lateral direction (p = 0.003), but not in the antero-posterior direction (p = 0.320). We found a difference in the angulation of the knees and heels depending on the sport played. Handball players showed higher knee varosity/valgosity (p = 0.015) and heel values than football players (p = 0.002). The handball players also confirmed a worse postural load and initial forward posture. The one-sided sports, handball and football, showed negative effects on the athlete’s movement system. These changes were more pronounced in handball players. Proper training programs should be applied in athletes’ daily routine to improve the negative effects of unilateral sports.